Change in the prevalence of myopia in Australian middle‐aged adults across 20 years. (19th August 2021) - Mackey, David A.; Lingham, Gareth; Lee, Samantha Sze‐Yee; Hunter, Michael; Wood, Diane; Hewitt, Alex W.; Mitchell, Paul; Taylor, Hugh R.; Hammond, Christopher J.; Yazar, Seyhan
Abstract: Background: The prevalence of myopia is increasing globally including in Europe and parts of Asia but Australian data are lacking. This study aim described the change in myopia prevalence in middle‐aged Australian adults over approximately a 20‐year period. Methods: Two contemporary Western Australian studies (conducted in mid‐late 2010s): the coastal‐regional Busselton Healthy Ageing Study (BHAS) and the urban Gen1 of the Raine Study (G1RS) were compared to two earlier studies (early‐mid 1990s) in Australia: the urban Blue Mountains Eye Study (BMES) and urban/regional Melbourne Visual Impairment Project (MVIP). Refractive error was measured by autorefraction, vertometry, or subjective refraction. Participants (49–70 years) of European descent without self‐reported/diagnosed cataract, corneal disease, or refractive or corneal surgery were included. Results: After exclusions, data were available from 2217, 1760, 700, 2987 and 756 participants from BMES, urban MVIP, regional MVIP, BHAS, and G1RS, respectively. The mean age ranged from 57.1 ± 4.6 years in the G1RS to 60.1 ± 6.0 years in the BMES; 44–48% of participants were male. When stratified by location, the contemporary urban G1RS cohort had a higher age‐standardised myopia prevalence than the urban MVIP and BMES cohorts (29.2%, 16.4%, and 23.9%, p  < 0.001). The contemporary coastal‐regional BHAS had a higher age‐standardised myopia prevalence than the regional MVIP cohort (19.4% vs. 13.8%, p  = 0.001). Conclusions: We report an increase in myopia prevalence in older adults in Australia born after World War ll compared to cohorts born before, accounting for urban/regional location. The prevalence of myopia remains relatively low in middle‐aged Australian adults.